Penerapan Konsep Syariah di Hannah Syariah Homestay Palu dan Kesesuaiannya dengan Fatwa DSN-MUI NO.108/DSN MUI/X/2016 Tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah - Fudhaylatullail Fudhaylatullail; Abdul Wahab Abd Muhaimin; Syarif Hidayatullah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Based on the DSN-MUI fatwa NO. 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles, sharia hotels have provisions that can guide hotel owners regarding products, services and their management based on sharia principles. This research is a qualitative type of research in the form of a case study. Researchers examined the application of sharia hotel products, services and management at Hannah Syariah Homestay Palu and their conformity with the DSN-MUI fatwa NO. 108/DSN-MUI/X/2016 concerning Guidelines for Tourism Implementation Based on Sharia Principles. the primary data was taken from data obtained from Hannah Syariah Homestay Palu and secondary data was taken from books and journals related to research. The results of the study show that first, the application of sharia hotel products at Hannah Syariah Homestay Palu provides yoga sports facilities which are still carried out in an open yard so that disobedience can occur. Second, the implementation of sharia hotel services at Hannah Syariah Homestay Palu does not yet have a prayer room for guests and employees. Third, the management of the sharia hotel at Hannah Syariah Homestay Palu does not yet have a Sharia Supervisory Board (DPS) to oversee the Shariah Homestay. Fourth, Hannah Syariah Homestay Palu has not fully implemented sharia hotel regulations. Of the 8 elements of sharia hotel provisions in the Fatwa, there are 2 elements that are not appropriate.